Shaping aggressive personality in adolescence: Exploring cross-lagged relations between aggressive thoughts, aggressive behaviour and self-control. (July 2016) - Murray, Aja Louise; Obsuth, Ingrid; Eisner, Manuel; Ribeaud, Denis
Abstract: Aggressive ideations can be defined as thoughts, daydreams or fantasies of harming another. They feature in theoretical models of aggressive behaviour causation and are used in violence risk assessments. Little is known, however, about long term relations between aggressive ideations, aggressive behaviour and related variables such as self-control. We examined cross-lagged associations between these variables in the most recent two waves of the Zurich project on social development (z-proso) when the participants were aged 15 and 17. We found that aggressive ideations were highly stable across this time span. The only significant cross-lagged effects were between aggressive behaviour at age 15 and self-control and aggressive ideations at age 17. Results are consistent with the strength model of self-control in which changes in specific self-controlled behaviour can produce generalised changes in self-control. They are also consistent with the hypothesis that aggressive ideations are more a reaction to or a reflection of shared causes with, rather than a cause of, aggressive behaviour. Future studies should aim to integrate measurements across short and long time scales in order to further understand the causal interactions between aggressive ideations and behaviours as they play out across at the state and trait level. Highlights: We examined cross-lagged associations between aggressive ideations, aggressive behaviour and self-control. Aggressive ideations were highly stable across approximately 2 years. Significant effects were from aggressive behaviour to aggressive ideations and self-control. These have implications for theories of aggression and self-control.